Mesozoic alkaline volcanism and mantle evolution of the southwestern São Francisco craton, Brazil - Bizzi, Luiz Augusto (Department of Geological Sciences, 2017)
This thesis explores the nature of the subcontinental lithosphere underlying the southwestern margin of the São Francisco craton and the relation of variations in the petrochemistry of kimberlites and related alkali igneous rocks to variations in age, thickness and thermodynamic history of their continental lithospheric hosts. The São Francisco craton is a mid- to late-Archean basement granite-greenstone terrain flanked to the west by the Proterozoic Tocantins Province (Almeida, 1977, Almeida et al., 1981). New Rb-Sr and Sm-Nd data are presented for both onand off-craton crustal rock sequences. The ultramafic greenstone association of the Rio das Velhas Supergroup yields 3.2 Ga Rb-Sr and Sm-Nd ages, in agreement with widespread 3.2 Ga old zircons from the area. Granitic gneiss and juvenile granitoids associated with the greenstones in the Congonhas area give a Transamazonian 2128 Ma Rb-Sr age, which is in agreement with a published 2124 Ma zircon age. Funher west, syntectonic granitoids and metabasalts from the Araxa Group define a 711 Ma Rb-Sr isochron. This latter age is interpreted as a Sr-isotope rehomogenization related to the development of the Brasilia orogenic and foreland thrust belt. A 823 Ma Sm-Nd errorchron indicate that these rocks may be coeval to the felsic volcanism of the Araxa Group which was recently dated at 794 Ma by zircon work (Pimentel et al., 1991). Funher to the west still, combined samples from the Nique!andia mafic-ultramafic igneous complex and associated granitic basement rocks yield a 1.26 Ga Rb-Sr isochron, which is best interpreted as a metamorphic age. Crystallization ages of the crustal sequences decrease and ENd values increase with increasing distance westward from the Archean craton margin. The isotopic characteristics are consistent with a model which requires that large volumes of crust, derived in the Proterozoic from mantle reservoirs similar to the sources for modern oceanic basalts, were accreted onto the pre-existing Archean nucleus during the Brasiliano orogenic event.